Solar Radiation on Photovoltaic Systems Deployed near Obscuring Walls - Joseph Appelbaum; Assaf Peled (Urban Science, 2025)
The deployment of solar photovoltaic (PV) systems on rooftops in urban environments utilizes the rooftop areas for electricity generation. Rooftops may provide a large amount of empty space that can reduce the use of land for large PV plant installations and other purposes. These deployments may encounter shading on the PV collectors from surrounding building walls, thus reducing the incident direct beam radiation on the PV collectors, resulting in shading losses. Moreover, walls and collector rows block part of the visible sky, reducing the incident diffuse radiation on the collectors, resulting in masking losses. The present study complements previous studies by the authors (see the references) by calculating the incident beam, diffuse and global radiation, and their distribution across the collector rows for four configurations of PV systems installed near obscuring walls. In addition, the article quantifies the shading problem by simulating the shading dimensions and their patterns caused by walls and collector rows. The article is of practical importance for designers of PV systems in urban environments. The simulation results indicate an almost uniform distribution of the incident radiation between the collector rows. On the other hand, the losses may reach 8 percent for a wall height of 4 m for the parameters used in the study.